Biofortification: An effective agricultural strategy for alleviating malnutrition - Praharaj, Subhashisa; Das, Usha; Singh, Rohitashav (Indian Farming, 2021)
Malnutrition is a global health issue and needs to be addressed with utmost urgency. In developing countries like India, the problem is even more serious and complicated. Improving the nutritional values of the staple crops can greatly help in improving the dietary intake of nutrients and thus reduce the problem of malnutrition to a great extent. Agronomic biofortification and genetic biofortification has been proven to improve the nutritional status of crops and can serve as a potential tool in ameliorating hunger and malnutrition.